The influence of the environment and work culture on organizational performance through strategic planning : at the Community and Village Empowerment Office of Flores Regency, East Nusa Tenggara Province - Mersiana Varia Juita (Institute of Accounting Research and Novation (IARN), 2022)
This study aims to determine the effect of environmental strategy, organizational culture, and planning strategy on organizational performance in the Village Community Empowerment Agency, the Provincial Government of Flores, East Nusa Tenggara. The sample of this research is 100 residents of Flores Regency. Partial Least Square (PLS) is used as a hypothesis testing tool. The results of the study show that organizational culture has an effect on organizational situations, and planning strategies have an effect on organizational performance, according to the findings of this study. In addition, the strategic environment influences the planning strategy, and organizational culture influences the planning strategy.